Carlos Saavedra Lamas y sus ideas acerca del Derecho Laboral en la Universidad de Buenos Aires - Boasso, Pedro Antonio (Res Gesta, 2022)
Labour law was initiated as an autonomous branch of the legal system at the beginning of the 20th century in response to the worrying situation of helplessness faced by a large number of workers. Jurists and men of government from different political lines participated in its development. This paper examines a distinguished lawyer’s ideas on the necessity to provide a legal response to the social issue. This lawyer was a Member of Parliament and a conservative- leaning politician.